I like it when-- Me gusta cuando-- - Murphy, Mary 1961-; Ada, Alma Flor.; Campoy, F. Isabel (Orlando Libros Viajeros/Harcourt, 2008)
A little penguin shares his favorite things with the one he loves most, his mother.
On board pages.
Cover title.
"Translated by F. Isabel Campoy and Alma Flor Ada"--P. [4] cover.
Parallel text in English and Spanish.
UCWS-3008g donated by Prof. Eric Julian Manalastas & Rommel Sta. Ana - June 2017
Keywords: Mother and child -- Fiction; Penguins -- Fiction; Bilingual books; Board books; Penguins -- Fiction; Spanish language materials -- Bilingual; Board books; Penguins -- Fiction; Parent-child relationship -- Fiction; Bilingual books -- English-Spanish.